Resummed heat kernel and effective action for Yukawa and QED - Franchino Viñas, Sebastián Alberto (2024)
In this letter, we prove the existence of resummed expressions for the diagonal of the heat kernel and the effective action of a quantum field which interacts with a scalar or an electromagnetic background. Working in an arbitrary number of spacetime dimensions, we propose an Ansatz beyond the Schwinger–DeWitt proposal, effectively resumming an infinite number of invariants which can be constructed from powers of the background, as well as its first and second derivatives in the Yukawa case. This provides a proof of the recent conjecture that all terms containing the invariants and ̃ in the proper-time series expansion of the SQED effective action can be resummed. Possible generalizations and several applications are also discussed—in particular, the existence of an analogue of the Schwinger effect for Yukawa couplings.